2011
DOI: 10.1111/j.1365-2052.2011.02267.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards standardization of canine STRs: a proposed nomenclature for six markers from the ISAG comparison‐test panel

Abstract: Eight short tandem repeat markers included in the International Society for Animal Genetics panel of 24 loci investigated in canine comparison tests were analysed in a sample of pure-breed dogs, with the purpose of defining an allele nomenclature based on the number of repeats. A regression analysis of the raw data produced by the sequencer, coupled with the direct sequencing of selected alleles, allowed us to propose a system of nomenclature for six of the eight loci (four di-nucleotidic: AHT121, AHTh137, REN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The definitive breed standard was approved by ENCI in February 1949 and nine months later, in November, the Società Amatori Bracco Italiano (Association of Italian Bracco Amateurs, SABI) was founded. At the present the studies on the genetic characterization by microsatellites of the Bracco Italiano breed, using ISAG panel as suggested by the international ISAG canine comparison test (Ciampolini et al, 2012), showed a low genetic variability of the breed (Ciampolini et al, 2011).…”
Section: Introductionmentioning
confidence: 74%
“…The definitive breed standard was approved by ENCI in February 1949 and nine months later, in November, the Società Amatori Bracco Italiano (Association of Italian Bracco Amateurs, SABI) was founded. At the present the studies on the genetic characterization by microsatellites of the Bracco Italiano breed, using ISAG panel as suggested by the international ISAG canine comparison test (Ciampolini et al, 2012), showed a low genetic variability of the breed (Ciampolini et al, 2011).…”
Section: Introductionmentioning
confidence: 74%
“…; Ciampolini et al . ). Recently, however, for production animals such as pigs ( Sus scrofa ) and cattle ( B. taurus ), a trend towards identification and parentage verification using single nucleotide polymorphisms (SNPs) has been observed (Rohrer et al .…”
Section: Discussionmentioning
confidence: 97%
“…The 19 microsatellites used in the analysis (Table 1 ) were located on 18 of the 39 chromosomes of the dog genome ( Canis lupus familiaris ); they are included in the “core panel” of loci recommended by the international society for animal genetics (ISAG) for parentage verification in the international canine comparison test [ 15 ]. The 19 microsatellites were co-amplified in a single multiplex PCR reaction.…”
Section: Main Textmentioning
confidence: 99%